Introducing the SMAP L4 Products and Investigating the Spatio-Temporal Variability of Soil Moisture in Iran - Ebrahim Asadi Oskouei; Leila Godarzy; Jalil Helali (Nīvār)
Background and objectives: Although estimation of soil surface moisture plays an important role in soil and water resources management, unfortunately, there is currently no national soil moisture monitoring network in Iran and the distribution of in situ measurement stations is irregular and some provinces do not have any measuring station. Hence, in recent years, numerous satellite-based methods have been developed for estimating and modeling the surface soil moisture. Active and passive microwave remote sensing provides a unique capability to obtain observations of soil moisture at global and regional scales. Therefore, aimed to quantitative estimation of soil moisture using L-band microwave radiometer, the main objective of the present study is to providing spatio-temporal maps of soil moisture using SMAP products and to interpreting the spatial and temporal variation of soil moisture throughout the country during the period 2015 to 2021. Materials and methods: Present study is conducted throughout the country during the period 2015 to 2021 and spatial and temporal soil moisture maps are prepared. The Soil Moisture Active Passive (SMAP) mission is quantitative estimation of soil moisture using L-band microwave radiometer at the global scale. It should be noted that SMAP Level-4 soil moisture data were used with a temporal resolution of 3 hour and a spatial resolution of 9 km which are available as the result of spatial and temporal interpolation of large-scale data (40 km). Results: Based on the findings of this study, 6 -year average of surface soil moisture (depth < 5 cm) indicates that surface soil moisture in the country ranged from 0.005 to 0.538 m3m-3 and the average surface moisture of the country was 0.137 m3m-3 during the mentioned period. Assessment of monthly average maps showed that the highest maximum monthly value (0.192 m3m-3) was occurred in February and the lowest monthly average of soil moisture (0.079 m3m-3) was occurred in August. Spatial assessment of the surface soil moisture suggests that the average annual soil moisture has been more in the northern and western regions of the country compared to other regions of the country, especially in comparison with the central and southeastern regions of the country. The evaluation of the results shows that Gilan province had the highest annual average soil moisture (0.294 m3m-3) during the mentioned period and after that, Mazandaran (0.243 m3m-3), Kohgiluyeh and Boyer-Ahmad (0.216 m3m-3) and Alborz (0. 209 m3m-3) provinces have the highest annual average soil moisture, respectively. Also, Sistan and Baluchestan (0.076 m3m-3), South Khorasan (0.091 m3m-3) and Yazd (0.096 m3m-3) provinces have the lowest annual average soil moisture. Conclusion: Knowledge of the amount of soil moisture is important in hydrological modeling studies, improving numerical weather prediction (NWP) models, intelligent irrigation in agriculture and climate change. Therefore, the results of this study can be applicable in soil and water resources management by knowing the amount of soil moisture in different time and region. Key words: L-band radiometry, Remote Sensing, Soil Moisture Active Passive (SMAP), Soil moisture